Designing an optimal infection prevention service: Part 1. Issue 1 (January 2023) - Burnett, Emma; Cooper, Tracey; Wares, Karen; Wigglesworth, Neil; Chiwera, Lilian; Settle, Chris; Robinson, Jude
Background: Healthcare-associated infections (HCAIs) pose a significant threat to the health and safety of patients, staff, and visitors. Infection prevention and control (IPC) teams play a crucial role in ensuring that systems and processes are in place to keep everyone safe within the healthcare environment. Aim: The aim of this study was to identify components of infection prevention services, priorities, indicators of successes and how they are measured, and facilitators and barriers to success. Methods: A s urvey questionnaire was developed and circulated to infection prevention leaders and managers. Findings/results: Seventy IPC leaders/managers completed the survey. Participants were responsible for a range of IPC services within and across healthcare organisations, with significant variations to IPC delivery components. Additionally, a range of budget availability was reported. Several IPC service requirements were considered core work of IPC teams, including providing IPC advice and support, surveillance and audit and education and training. Discussion: An optimal IPC service needs to be in place to ensure HCAIs are minimised or prevented. In a post pandemic era, this is more important than ever before. This is also as crucial for the health and wellbeing of those working in IPC, who have endured unprecedented demand for their services during the pandemic.